Exploration of Risk Factors for Suicidal Ideation in Depressed Adolescents - Mariyati Mariyati; Arifianto Arifianto (Sekolah Tinggi Ilmu Kesehatan Kesdam IV, Diponegoro Semarang, Indonesia, 2024)
Background: Adolescents are a vulnerable group for mental health problems, one of which is depression. Research on adolescents with depression with suicidal ideation in the General Hospital Polyclinic is still very rare. Adolescents who undergo depression treatment while in the RSU Polyclinic need to know the cause and how resilient they are to their suicidal ideation to be the basis for further intervention. Research Objective: This study aims to explore the risk factors for suicidal ideation in adolescents who experience depression in the Mental Health Polyclinic of Permata Medika Hospital. Methodology: Phenomenological studies are used as an appropriate method to explore the resilience experiences of adolescents with suicidal ideation who experience depression. Data collection was carried out through in-depth interviews with semi-structured interview guidelines. The participants in this study were 6 young adults who experienced depression. Data analysis used Colaizzi's theory with the stages of data transcription, significant statements, formulating categories, sub-themes and themes contained in significant statements. Results: The data analysis process found 2 themes consisting of risk factors for suicidal ideation: 1) Internal factors consisting of a closed and ambitious personality and physical illness, 2) External factors consisting of unpleasant experiences (bullying, loss, trauma, parental separation), parenting patterns, and unfulfilled desires. Conclusion: Depression and suicidal behaviour are closely related. The causes of suicide from parenting patterns in the family, closed personality, bullying, relationship problems and physical illnesses that result in prolonged sadness, distrust, depression, self-harm behavior to suicide.